Pattern of haemostatic parameters and their relationship with microalbuminuria among hypertensives in Northern Nigeria - Ijei IP; Bello-Manga H; Yusuf R; Sani B; Mamman A (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background:Hypertension is a common, non-communicable disorder of public health significance.Abnormalities in haemostasis and blood rheology have been linked to target organ damage (TOD) in hypertension. Microalbuminuria (MA) is an independent predictor of TOD. Methods:A cross-sectional study was carried out among 107 consecutively recruited hypertensives attending the Cardiology Clinic at ABUTH, Zaria, Nigeria. Complete blood counts, haemostaticscreening tests and microalbuminuria assay were performed on blood and urine specimens. Results:The mean age of participants was 50.2±11.3 years and 59.3±18.2 years for females and males respectively with a female predominance (91/107; 85%). The frequencies of abnormal platelet counts, prothrombin time, activated partial thromboplastin time, thrombin time, fibrinogen, D-dimer and MA were 15%, 57%, 54.2%, 64.5%, 100%, 25.2%, and 41% respectively.Participants with poor BP control had an increased risk of derangements in aPTT and platelet counts(OR=1.4, 1.4) but there was no significant difference in means with BP for aPTT, fibrinogen, and platelets (p=0.517, 0.257 and 0.525 respectively). The impact of the duration of hypertension was shown in D-dimer levels up to 10years. Participants on ARB/ACEI-containing regimens showed a higher risk of derangement in TT, aPTT, PT and D-dimer in contrast to platelet counts (OR=0.96, p=0.836). Haemostatic parameters showed weakly positive, statistically significant correlation on regression analysis. Conclusion:There is a high prevalence of, and positive correlation between haemostatic abnormalities and MA among hypertensives in Northern Nigeria. Abnormal haemostatic screening tests may indicate MA and increased risk of TOD.